Deadlock Solving in Transport System with Methods from Computer Operating System - Zarnay, Michal (Communications - Scientific letters of the University of Zilina, 2003)
In its first part, the article compares control principles in computer operating systems and in transport systems, and outlines similarities. One part of the control in both systems is handling of deadlock situations. When replacing human control by computer control in transport systems, handling of deadlock situations must be tackled as well. In its second part, the article outlines algorithms used in the operating systems field for that and discusses their potential application in the transport systems field. It comes to a conclusion that avoidance of deadlock by dynamic analysis of requested and assigned resources to processes looks to be the most perspective way generally, although in specific systems, rules for prevention or detection and recovery from deadlock can be also applied.